Intermittent calorie restriction enhances epithelial-mesenchymal transition through the alteration of energy metabolism in a mouse tumor model - Kusuoka, Osamu (Int J Oncol, 2017)
The effect of intermittent calorie restriction (ICR) on cancer is controversial. In this study, we examined the effects of ICR and food content in syngeneic BALB/c mice injected with CT26 mouse colon cancer cells. Mice were subjected to 24-h fasting once a week for 4 weeks, and then provided with a control, high-calorie, or trans fatty acid-rich diet. While ICR resulted in increases in tumor weights, metastasis and in the number of cancer stem cells (CSCs) in the tumors or blood of mice fed the control and high-fat diets, it had no effect on body weight after 4 weeks. In particular, we detected increases in the numbers of CSCs in the tumor or blood on the day after starvation, when food overconsumption was detected. Conversely, continuous calorie restriction had no effect on tumor weight, metastasis, or the number of CSCs in tumors or blood. In the post-starvation period, energy metabolism in the tumor was altered from oxidative phosphorylation to glycolysis/lactate fermentation, with the acquisition of the epithelial-mesenchymal transition (EMT) phenotype. Hyperglycemia at the post-starvation period induced the expression of insulin-like growth factor-1, hypoxia-induced factor-1α and Nanog, as well as the phosphorylation of Stat3. Taken together, these findings suggest that ICR induces an increase in the number of CSCs and enhances EMT by promoting the Warburg/Crabtree effect following post-fasting food overconsumption.